The Adaptation of artificial intelligence in the malaysian construction industry / Mohammad Ashril Nadzim Abu Seman - Mohammad Ashril Nadzim, Abu Seman (2018)
The construction industry is a knowledge-intensive based because it involves a massive amount of data. With the involvement of enormous data processing, it has led to the development of Artificial Intelligence on knowledge management. Artificial Intelligence technology possessed the ability to represent knowledge and reason with it thus enable for decision making in a wide variety of situations. However, there are several issues in regards to the adaptation of Artificial Intelligence in the Malaysian construction industry, where there is only limited usage of the technology and the attitudes of the industry itself that remain conservative. The aim of this paper is to investigate the level of adaptation on Artificial Intelligence in the Malaysian construction industry. In line with this aim, three research objectives had been developed; (a) explore the levels of Artificial Intelligence adaptation in the Malaysian construction industry, (b) to identify barriers on adapting Artificial Intelligence in the Malaysian construction industry, and (c) to recommend solutions to enhance usage of Artificial Intelligence in the Malaysian construction industry. Conceptual review is used in this paper by compiling and summarising literature from leading articles, journals, books, and proceedings in regards to the study area. The outcome of this review paper shall present the variables and parameters of the Artificial Intelligence in the Malaysian construction industry. Optimistically with this study, the Malaysian construction industry can adapt more intelligent systems concept into practices in the future.